Fine control of metal concentrations is necessary for cells to discern zinc from cobalt. Issue 1 (December 2017) - Osman, Deenah; Foster, Andrew; Chen, Junjun; Svedaite, Kotryna; Steed, Jonathan; Lurie-Luke, Elena; Huggins, Thomas; Robinson, Nigel
Abstract Bacteria possess transcription factors whose DNA-binding activity is altered upon binding to specific metals, but metal binding is not specific in vitro. Here we show that tight regulation of buffered intracellular metal concentrations is a prerequisite for metal specificity of Zur, ZntR, RcnR and FrmR inSalmonella Typhimurium. In cells, at non-inhibitory elevated concentrations, Zur and ZntR, only respond to Zn(II), RcnR to cobalt and FrmR to formaldehyde. However, in vitro all these sensors bind non-cognate metals, which alters DNA binding. We model the responses of these sensors to intracellular-buffered concentrations of Co(II) and Zn(II) based upon determined abundances, metal affinities and DNA affinities of each apo- and metalated sensor. The cognate sensors are modelled to respond at the lowest concentrations of their cognate metal, explaining specificity. However, other sensors are modelled to respond at concentrations only slightly higher, and cobalt or Zn(II) shock triggers mal-responses that match these predictions. Thus, perfect metal specificity is fine-tuned to a narrow range of buffered intracellular metal concentrations. Bacteria possess transcription factors whose DNA-binding activity is altered upon binding to specific metals, but the binding of metals is not specific in vitro. Here, Osman et al. show that tight regulation of buffered intracellular metal concentrations is a prerequisite for metal specificity.